On the peculiarities of experiencing the loss of a spouse by women of different age categories - V. V. Kozyreva; O. Yu. Nikolaeva (Вестник университета)
The process of experiencing the loss of a spouse is called one of the most difficult life shocks. Often this period is quite long and includes overcoming and processing feelings such as guilt, confusion, fear, and others. Also, grieving for a spouse can cause serious damage to mental and physical health. The mourning associated with the loss of a spouse is a process in which it is possible to identify features, that is, what distinguishes it from other similar emotional shocks (loss of a friend, close relative). The specificity of experiencing the loss of a spouse, in particular, is expressed in the fact that not only the individual characteristics of a woman, but also the social and age characteristics of her personality are of great importance.